The Wireshark field guide analyzing and troubleshooting network traffic - Shimonski, Robert (Syngress, 2013)
Annotation
Online resource; title from title page (ebrary, viewed June 08, 2013)
Keywords: Computer network protocols; Computer networks -- Maintenance and repair; Computer networks -- Management; Protocoles de réseaux d'ordinateurs; Réseaux d'ordinateurs; Entretien et réparations; Réseaux d'ordinateurs; Gestion; Computer networks; Maintenance and repair; Computer networks; Management